Assessment of Inclusive Education among Mega High Schools in SOCCSKSARGEN Region - Kurt B. Catolico; Epimaco A. Cabanlit Jr. (East Asian Journal of Multidisciplinary Research, 2023)
The study aimed to determine the implementation level of inclusive education among mega high schools within the SOCCSKSARGEN region in the Philippines. Descriptive quantitative and qualitative research designs were employed to describe inclusive education implementation. The study encompassed input from school principals and teachers from four mega high schools, selected via cluster sampling. The findings showed a high implementation level of inclusive education among the respondents and were influenced by several challenging factors resulting in an impact evaluation integrating the theory of change. Over the long term, inclusive education implementation could bring about tangible societal benefits, upholding every student's right to education, aiding social integration, reducing discrimination, promoting equality, and eventually contributing to the development of a more inclusive society.